2008
DOI: 10.1016/j.neubiorev.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction: A potential cognitive marker of psychiatric disorders

Abstract: Cognitive deficits are well documented in psychiatric disorders, particularly in schizophrenia and depression. Cognitive activity roots in perceptions. However, research on sensorial alterations in psychiatric conditions has mainly focused on visual or auditory processes and less on olfaction. Here, we examine data on olfactory deficits in psychiatric patients using a systematic review of recent publications. Schizophrenic patients are mainly characterized by no reliable change in odour sensitivity and by a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
150
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(166 citation statements)
references
References 141 publications
4
150
0
12
Order By: Relevance
“…Deficits in odor discrimination in schizophrenia have, by now, also become well documented. 50,51 Although early literature on olfactory deficits tended to focus on issues such as hedonics and potential limbic involvement, subsequent studies demonstrated severe impairments even at the level of identification and discrimination. NMDA receptors are known to play a critical role in olfactory processing, particularly in processes such as discrimination and habituation.…”
Section: Other Sensory Systemsmentioning
confidence: 99%
“…Deficits in odor discrimination in schizophrenia have, by now, also become well documented. 50,51 Although early literature on olfactory deficits tended to focus on issues such as hedonics and potential limbic involvement, subsequent studies demonstrated severe impairments even at the level of identification and discrimination. NMDA receptors are known to play a critical role in olfactory processing, particularly in processes such as discrimination and habituation.…”
Section: Other Sensory Systemsmentioning
confidence: 99%
“…These new generation of portable olfactometers, will certainly allow a large number of applications, comprising those related to enhancing the sense of presence in virtual reality environments. These devices will also contribute to investigating perceptual, emotional, and retention-related (memory) aspects of olfaction in humans, as well as be part of multisensory rehabilitations techniques for a number of neuropsychological disorders (Atanasova et al, 2008;Baba et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…23,[33][34][35] Some investigators theorize that olfactory declines may be a consequence of autoimmune mechanisms 36 or neurodegenerative diseases. 37 The prognosis of olfactory dysfunction is influenced by certain demographic and clinical factors. Over time, regaining the sense of smell is more likely in females, 38 younger persons, 38,39 those with lesser severity of initial olfactory loss, 39 and those with shorter duration of dysfunction.…”
Section: Discussionmentioning
confidence: 99%